2021
DOI: 10.3390/su13126841
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sustainable Leadership amongst Female Managers in the Spanish Logistics Industry: A Cultural, Ethical and Legal Perspective

Abstract: At present, the logistics industry in Spain is one that is mostly male-dominated, and women middle and top managers make up less than 10% of the workforce at these management levels. There is therefore an obvious lack of parity in this sector. Spanish regulation at present supports and promotes gender parity in different sectors including the logistics industry. Our article uses as a basis the fifth Sustainable Development Goal, “achieve gender equality and empower all women and girls”. Twenty-four female midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Many indigenous populations, such as the Wayuu one, are accustomed to humanize and identify male and female genders with meteorological phenomena, with the stars, the sun, the earth, and the moon, and with a number of elements of the native land where they coexist [62]. Thus, they assume that leadership positions are open to dialogue and to collaborative work [63], and their initiatives are characterized by respect for values and principles and by the dissemination of collective actions.…”
Section: Discussionmentioning
confidence: 99%
“…Many indigenous populations, such as the Wayuu one, are accustomed to humanize and identify male and female genders with meteorological phenomena, with the stars, the sun, the earth, and the moon, and with a number of elements of the native land where they coexist [62]. Thus, they assume that leadership positions are open to dialogue and to collaborative work [63], and their initiatives are characterized by respect for values and principles and by the dissemination of collective actions.…”
Section: Discussionmentioning
confidence: 99%
“…The core objective of frugal innovation is to promote intergenerational equity and environmental justice ( Von Zedtwitz et al, 2015 ), a crucial concern in sustainable leadership ( Bulmer et al, 2021 ). Its practices revolve around practical communication skills and awareness of diverse stakeholders’ cultural backgrounds and values.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lyness and Hilman (2006) found that women in staff jobs received lower performance ratings than men. Nevertheless, there is still a considerable need for improvement, particularly regarding management practices in the logistics sector (Bulmer et al ., 2021). An initiative is required in the logistics firms' promotion system to address the problem of better usage, potential and female leadership in logistics (Tadić, 2021).…”
Section: Introductionmentioning
confidence: 99%